Program Kedaulatan Pangan di Indonesia : Studi terhadap Indonesia-Australia Partnership on Food Security in the Red Meat and Cattle Sector - Sinta Windy Anggraeni; Bagus Sigit Sunarko; Pra Adi Soelistijono (University of Jember, 2023)
Food security is a multidimensional and complex issue, as well as a vital primary need for society. In this regard, food security has a close relationship with productivity. Foodstuffs included in food security are not only limited to vegetable food ingredients such as rice, corn and potatoes or other tubers but also include side dishes or animal food ingredients, for example, beef. Indonesia often cannot meet the demand for beef due to the limited national supply of beef. This situation is the cause for Indonesia needing beef supply assistance from other countries to be able to stabilize the condition of the pagan demand for beef for Indonesian citizens which is increasing in line with increasing population and also increasing food needs in the beef sector. As an effort to offset the increasing demand for beef, Indonesia and Australia agreed to form a partnership in a related sector called the